The antecedents of pro-environmental behavior: Environmental commitment, environmental consciousness, green lifestyle, and green self-efficacy - Nidhana, Nabila Nadlif; Khoirunnisa, Rikha Muftia; Hendrawan, Suryana (Journal of Management and Business Insight, 2025)
Purpose-Environmental issues are currently a serious problem faced by all sectors of society. Green lifestyle changes need to be encouraged from an early age to promote pro-environmental behavior. This study examines the influence of environmental commitment, environmental awareness, green lifestyle, and green self-confidence on pro-environmental behavior. Methodology-This study used a quantitative approach with a survey method through questionnaires. The research data was obtained from 320 respondents selected using convenience sampling techniques. Data analysis was carried out through validity and reliability tests and hypothesis testing using SPSS version 20. Findings-The results of the study indicate that environmental commitment, green lifestyle, and green self-efficacy have a positive influence on pro-environmental behavior. However, environmental awareness does not significantly influence pro-environmental behavior, suggesting that awareness alone cannot be transformed into actionable behavior without other reinforcing factors. Research Limitations-The scope of this study focuses on students of public vocational high schools in Yogyakarta, Indonesia. Therefore, the results cannot represent other school levels and regions outside Yogyakarta. Novelty-This study provides a deeper understanding of the relationship between pro-environmental behavior and its influencing factors. These findings are expected to offer practical recommendations for policymakers and practitioners to improve pro-environmental behavior.